Protecting the SWAP operation from general and residual errors by continuous dynamical decoupling - Fanchini, F. F. [UNESP]; Napolitano, R. D.J.; Çakmak, B.; Caldeira, A. O. (American Physical Society (APS), 2015)
We study the occurrence of errors in a continuously decoupled two-qubit state during a SWAP quantum operation under decoherence. We consider a realization of this quantum gate based on the Heisenberg exchange interaction, which alone suffices for achieving universal quantum computation. Furthermore, we introduce a continuous-dynamical-decoupling scheme that commutes with the Heisenberg Hamiltonian to protect it from the amplitude damping and dephasing errors caused by the system-environment interaction. We consider two error-protection settings. One protects the qubits from both amplitude damping and dephasing errors. The other features the amplitude damping as a residual error and protects the qubits from dephasing errors only. In both settings, we investigate the interaction of qubits with common and independent environments separately. We study how errors affect the entanglement and fidelity for different environmental spectral densities.